PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN BOOKLET TERHADAP KEAKTIFAN DAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI MEKANISME KATUP KELAS XI TSM SMK YPT PURWOREJO - Ikhsan Asidiq Sudrajat; Widiyatmoko; Arif Susanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of applying the Problem Based Learning (PBL) model assisted by booklet on the activeness and cognitive learning outcomes of students in the valve mechanism material for class XI TSM SMK YPT Purworejo. This research uses a quasi-experimental method with a pretest-posttest control group design. The research subjects were students of class XI TSM SMK YPT Purworejo consisting of an experimental class and a control class. Data on student activeness were obtained through observation sheets, while cognitive learning outcomes data were obtained through pretest and posttest. The data analysis techniques used are descriptive statistical tests, normality tests, homogeneity tests, and sign tests. The results showed that (1) there were differences in the application of the PBL model assisted by booklet on student activeness, (2) there were differences in the application of the PBL model assisted by booklet on students' cognitive learning outcomes, (3) there was an influence of the application of the PBL model assisted by booklet on student activeness and cognitive learning outcomes. Student activeness in the experimental class increased from 57% to 74%, while the average learning outcome increased from 43 with a percentage of 13% to 81 with a percentage of 82.6%. These results prove that the application of the PBL model assisted by booklet is effective in improving student activeness and cognitive learning outcomes on valve mechanism material.